Misconception in Physics Learning: A Systematic Review of the Research Trend, Misconception Profile, Diagnosis, and Remediation Strategies - Marjana, Reja; Achmad Samsudin; Duden Saepuzaman; Dadi Rusdiana (Universitas Muhammadiyah Makassar, 2026)
Misconceptions in physics education continue to be a persistent challenge because they hinder meaningful learning, weaken conceptual understanding, and reduce students’ ability to accurately interpret physical phenomena. Although research on this topic has grown over the past decade, the literature remains fragmented across different educational levels, physics topics, diagnostic approaches, and remediation strategies. This study aimed to provide an updated and structured overview of influential research on misconceptions in physics by analyzing research trends, misconception profiles, diagnostic tools, and remediation techniques. A citation-based systematic mapping review was conducted using the Scopus database. The search was limited to English-language journal articles and conference proceedings published between 2015 and 2024, with the top 100 records ranked by citation count screened, resulting in 74 studies included in the final analysis. The results show that research on misconceptions in physics primarily focuses on university and high school students, with classical mechanics the most studied topic, followed by electricity, magnetism, and wave-related concepts. In terms of diagnosis, four-tier diagnostic tests were the most frequently used instruments, followed by established concept inventories such as the Force Concept Inventory. Concerning remediation, diagnostic-based interventions, conceptual change strategies, and cognitive conflict-based learning were the most prominent approaches. However, a significant number of studies did not explicitly identify the causes of misconceptions or report clear remediation strategies. The novelty of this review lies in its integrative mapping of influential studies across multiple analytical dimensions within a single physics-specific framework. This research contributes to physics education by offering a structured reference for future work on diagnostic development, causal analysis, and the design of more context-sensitive instructional interventions.